Inovasi Dan Optimalisasi Proses Produksi Sirup Bunga Rosella Di Desa Karangtengah Kabupaten Kendal - Nayla Faizah; Nayli Fadhilah; Nabil Zainul Fikri; Moh Iqbal Assidiqi; Syauqi Muhsinatur Rohmani; Muhammad Ikhwal Afrizal; Balda Rafi Ardian; Ellza Nafisah Maghfiroh; Hafidha Asni Akmalia (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
The main focus of this research is to deeply analyze the existing production process, evaluate the technology and equipment used, and identify ways to improve raw material and energy management. Through the application of the latest technology, such as more efficient processing machines and more modern processing methods, it is expected to improve production efficiency, reduce operational costs, and ensure consistent product quality. The research method includes data collection from observations of the current production process, interviews with local producers, and analysis of the equipment and techniques used. In addition, this research also involves testing the implementation of innovations and evaluating their impact on the final product results and production costs. The expected results of this research include improved syrup quality, better operational efficiency, and reduced production costs, which overall can increase the competitiveness of Karangtengah syrup products in the market. The benefits of this research are not only limited to improving the quality and efficiency of production but also include positive economic impacts for the local community. By improving the production process and expanding market reach, it is expected to create new economic opportunities, improve the welfare of local communities, and provide a model for other food processing industries in the region. This research aims to make a significant contribution to the development of the local industry and encourage the adoption of more sustainable and innovative production practices.